Bioethics for physicians.Telling the truth (Discourse of Law and Administration, 2019)
The standard of physician professional behavior towards patients has changed a lot over the past 30 years. From physicians patients dement not only the necessary information about their health but also physicians are expected to communicate important information to patients related to treatment decisions. The purpose of truth telling is not simply to enable patients to make informed choices about health care and other aspects of their lives but also to inform them about their situation. On the basis of truth telling grows trust between patient and the physician which is based on the respect owed to patients as persons. How in this contest we should we understand the “therapeutic privilege” known in Polish law? True telling, also often prevents harm, as patients who are uninformed about their situation may fail to get medical help when they should.
Keywords: patients’ rights; true telling; patients autonomy; therapeutic privilege